METHODOLOGY FOR DEVELOPING STUDENTS' TECHNICAL CREATIVITY BASED ON THE STEM APPROACH USING THE EXAMPLE OF TEACHING PHYSICS - Absalyamova Ilmira Ildarovna; Abdullayeva Shoira Isajanovna; Ochilova Ozoda Odilovna; Xalilova Nozliya Samadovna (Bright Mind Publishing, 2025)
This article explores methodological principles for fostering students' technical creativity through the STEM approach, specifically in the context of physics education. It outlines strategies for integrating science, technology, engineering, and mathematics to enhance hands-on learning and problem-solving. The article analyzes existing literature, presents practical styles of teaching, and discusses the effectiveness of the STEM approach in nurturing innovation among students. Findings indicate that well-designed STEM-based physics instruction significantly boosts students' creative and technical thinking.
Keywords: STEM, technical creativity, physics education, innovation, problem-based learning, project-based learning, interdisciplinary teaching.